2021
DOI: 10.3390/ijms23010105
|View full text |Cite
|
Sign up to set email alerts
|

Renal Tissue miRNA Expression Profiles in ANCA-Associated Vasculitis—A Comparative Analysis

Abstract: Anti-neutrophil cytoplasm antibody (ANCA)-associated vasculitis (AAV) comprises autoimmune disease entities that cause target organ damage due to relapsing-remitting small vessel necrotizing vasculitis, and which affects various vascular beds. The pathogenesis of AAV is incompletely understood, which translates to considerable disease- and treatment-related morbidity and mortality. Recent advances have implicated microRNAs (miRNAs) in AAV; however, their accurate characterization in renal tissue is lacking. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Several tissue types are used for biomarker research in SNV and are shown in Table 1 [52][53][54][55][56]. A definitive diagnosis of necrotic vasculitis is based on the histological confirmation of necrosis in the vessel wall on the biopsy of an affected area.…”
Section: Advances In Biomarker Researchmentioning
confidence: 99%
“…Several tissue types are used for biomarker research in SNV and are shown in Table 1 [52][53][54][55][56]. A definitive diagnosis of necrotic vasculitis is based on the histological confirmation of necrosis in the vessel wall on the biopsy of an affected area.…”
Section: Advances In Biomarker Researchmentioning
confidence: 99%